Comparison of Total Knee Arthroplasty Outcomes Between Renal Transplant and End Stage Renal Disease Patients. (March 2022) - Stavrakis, Alexandra I.; Li, Alan K.; Uquillas, Carlos; Photopoulos, Christos
Abstract : Introduction: Patients with end-stage renal disease (ESRD) have increased risk for periprosthetic joint infection (PJI) due to their predisposition for bacteremia and subsequent implant inoculation secondary to dialysis. PJI risk is also elevated in transplant patients secondary to chronic immunosuppressive therapy. The purpose of this study was to compare medical and surgical complications after primary total knee arthroplasty (TKA) in patients with ESRD or renal transplant (RT). Methods: This was a retrospective review from the PearlDiver database. International Classification of Diseases and Current Procedural Terminology codes were used to identify patients with ESRD or RT who underwent primary TKA for osteoarthritis from 2015 to 2019. Univariate and multivariable logistic regression analyses were done for medical complications up to 90 days and surgical complications up to 2 years. Results: Within 90 days of TKA, patients with RT were less likely to develop pneumonia (odds ratio [OR] 0.46, 95% confidence interval [CI] 0.23 to 0.84, P = 0.018) and wound dehiscence (OR 0.46, 95% CI 0.21 to 0.90, P = 0.015). Patients with RT had a lower risk for PJI at 1 year (OR 0.61, 95% CI 0.36 to 0.99, P = 0.017) and at 2 years (OR 0.56, 95% CI 0.34 to 0.88, P = 0.017) after primary TKA. Discussion: Consideration should be given to delaying TKA in patients with ESRD who are RT candidates.